There goes the neighborhood : rural school consolidation at the grass roots in early twentieth-century Iowa - Reynolds, David R. (University of Iowa Press, 1999)
Despite being the centerpiece of rural educational reform for most of the twentieth century, rural school consolidation has received remarkably little scholarly attention. The social history and geography of the movement, the widespread resistance it provoked, and the cultural landscapes its proponents sought to transform have remained largely unexplored. Now in There Goes the Neighborhood David Reynolds remedies this situation by examining the rural school consolidation movement in that most midwestern of midwestern states, Iowa.